2020
DOI: 10.1017/dap.2020.14
|View full text |Cite
|
Sign up to set email alerts
|

Emerging health data platforms: From individual control to collective data governance

Abstract: Health data have enormous potential to transform healthcare, health service design, research, and individual health management. However, health data collected by institutions tend to remain siloed within those institutions limiting access by other services, individuals or researchers. Further, health data generated outside health services (e.g., from wearable devices) may not be easily accessible or useable by individuals or connected to other parts of the health system. There are ongoing tensions between data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“… 33 They also get to elect some of the members of the Open Humans Foundation board of directors, enabling them to participate in the broader governance of the platform. 33 , 43 This configuration contributes toward enabling accountability and transparency in the use of data in such a way that participants' data contribution is not used beyond their intention, such as health profiling based on stereotypes for governance and commercial purposes and loss of privacy.…”
Section: Resultsmentioning
confidence: 99%
“… 33 They also get to elect some of the members of the Open Humans Foundation board of directors, enabling them to participate in the broader governance of the platform. 33 , 43 This configuration contributes toward enabling accountability and transparency in the use of data in such a way that participants' data contribution is not used beyond their intention, such as health profiling based on stereotypes for governance and commercial purposes and loss of privacy.…”
Section: Resultsmentioning
confidence: 99%
“…There is a trade-off between the scientific desirability of everyone contributing de-identified data, including to avoid bias, 76 77 and the desirability of individual control over data use. 78 As we suggest below, a reasonable balance might be a central system to opt out from identifiable clinical use, identifiable (§251) research use, or de-identified research use of one’s data, and to opt in for participatory research. This would complement efforts to improve people’s access to their own data.…”
Section: Discussionmentioning
confidence: 99%
“…Participants supported a central system for patients to control the uses of their data, and likewise a single NHS mechanism to sign up for active research participation. There is a trade-off between the scientific desirability of everyone contributing de-identified data, including to avoid bias,76 77 and the desirability of individual control over data use 78. As we suggest below, a reasonable balance might be a central system to opt out from identifiable clinical use, identifiable (§251) research use, or de-identified research use of one’s data, and to opt in for participatory research.…”
Section: Discussionmentioning
confidence: 99%
“…Through the implementation of participatory data governance frameworks, institutions can involve citizens in establishing the principles by which data is used (Micheli et al., 2020). Models such as civic data trusts, where data are held by an independent party and who facilitate participation by stakeholders in decisions regarding data access, sharing and use, could reduce the barriers to data governance (Kariotis et al., 2020). Such a process of citizen engagement in broader decisions around data privacy and governance is necessary to move beyond assumptions that privacy is simply about the limitations of data sharing.…”
Section: Additional Considerationsmentioning
confidence: 99%